Optimization of electron Beam properties for generation of coherent THz undulator radiation at PBP-CMU linac laboratory - Chaisueb N. (2017)
Copyright © 2016 CC-BY-3.0 and by the respective authors. Relativistic femtosecond electron bunches produced from the linear accelerator at the Plasma and Beam (PBP) Physics Research Facility are currently used to generate THz radiation via transition radiation. An upgrade to increase the intensity of the THz radiation by using a coherent undulator radiation method is conducted. Optimizations, measurements and analysis of the electron beam properties, which include current, energy and energy spread as well as electron bunch length, are performed to investigate the capability of electron beam production from the current accelerator system. This is also to estimate the possibility to produce the coherent undulator radiation of the PBP-CMU linac. Expected characteristics of the coherent undulator radiation are studied and reported in this contribution.